Perancangan Video Promosi Tinctori Sebagai Media Promosi dengan Penerapan Marketing 5.0 - Samuel Brian Nanda; Martin Setyawan; Michael Bezaleel Wenas (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2025)
This study discusses the design of a promotional video for Tinctori by implementing marketing 5.0 to enhance the effectiveness of marketing sustainable products. Tinctori is a fashion company that utilizes natural dyes, supporting the concept of sustainable fashion and the Sustainable Development Goals (SDGs). However, its current promotional strategy has not been optimal in capturing the attention of its target audience, particularly the upper-middle-class consumers who are environmentally conscious. The findings indicate that applying cinematography in promotional videos can enhance visual appeal, audience engagement, and understanding of Tinctori’s sustainability values. The designed video showcases the natural dyeing process with artistic, transparent, and emotional visuals, strengthening brand identity and increasing consumer purchase interest. Evaluations from videography experts and the target audience confirm that the video effectively conveys the sustainability message and raises awareness of environmentally friendly fashion.